Vallejian Ecdotics: Four Models and a Reorientation towards the Edition of Texts of Literary Criticism - Flores Heredia, Gladys (2022)
This article systematizes and shows the four models of edition followed by the ecdotica on Vallejo’s poetry. Each of them is framed in the historiographical context that goes from the sixties of the 20th century (pre-critical edition and critical edition) to the second decade of the 21st century (diplomatic edition). The historiographical and analytical explanation of these editions reveals the insistence on replicating models of editing, and not on innovating them; therefore, the need to reorient Vallejo’s ecdotics towards the critical texts that established the first protocols of reading about the life and work of César Vallejo is proposed, among these, the legal-critical approach that Germán Patrón Candela describes in the text El proceso Vallejo (The Vallejo Process, 1992). To this end, the princely edition is examined, as well as the second and third editions. The hermeneutic necessity of fixing the critical text is emphasized in order to encourage re-readings that produce meaning from the critical sources.